Nilai Gaya Tekan Yang Dibutuhkan Oleh Dinding Pemecah Dalam Memecahkan Nut Pada Stasiun Ripple Mill - Herry Darmadi (Jurnal Teknik Mesin dan Mekatronika (Journal of Mechanical Engineering and Mechatronics), 2023)
Ripple mill is there at the kernel station. The function of this ripple mill is that of a breaking or breaking shell from the sawmill's core by having a centrifugal (far from the center of spin) that produces ripple mills, which releases the seed from the rotor and gives it a powerful impact that causes the shell to shatter. The principle of ripple mill is that a pinch, a grinding of beans between the gaps a cistern rotorassembly with the ripple mill plate. It's called a saw seed that feeds from above the ripple mill and gets it repeatedly between the ripple plate and the moving rotor. The pressure style is a force that tends to press or destroy material. In the industry we also employ ripple mill force, for example. The sliding voltage is a stylistic link alluding to the surface of an expanding cross-section. This study aims to know how much pressure force is needed for ripple mills during the shell- breaking process, and how much slide tension occurs to the stake in the shell- breaking process. From the research that has been done, the pressure force that wall breakers need to break the nut at 31.18 n for the process to break down properly, and the shifting tension that occurs in a stake of 0.0686 n /mm2 so that the stake can last longer in its usage of ripple mill.